(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The aim of the research to apply TD-ABC technology to determine the idle capacity of the central oil companies (oil field east of Baghdad), as a modern cost management technology based on time-oriented activities (TD-ABC) is used by industrial companies in general and oil companies on In particular to build a sustainable Calvinist pillar and make future decisions by identifying idle energy to gain it a competitive advantage, the descriptive analytical approach has been adopted in calculating and analyzing the company’s data for 2018, and the most prominent conclusions of this research are managing idle energy and the task of applying cost technology on the basis of time-oriented activities and providing Convenient spatial information through a more equitable distribution of costs on petroleum products to determine the cost per barrel of oil by the company’s management.